2016
DOI: 10.1097/brs.0000000000001254
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Cognitive-Behavioral Patient Education Versus Standard Care for Lumbar Spinal Fusion Patients

Abstract: Preoperative CBT appears to be more effective and cost neutral when considering the overall health care sector and labor market perspective, supporting the implementation of preoperative CBT in the course of treatment for LSF surgery in a Danish context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 25 publications
0
46
0
Order By: Relevance
“…Health-related quality of life is a key outcome in the management of LSS and its assessment during clinical practice may suggest the introduction of psychological interventions directed at promoting psychological resources in the patient with the aim to improve long-term outcome or even enhance recovery. Indeed, cognitive-behavioural patient education has been proven effective for the improvement of both clinical and quality-of-life outcomes in these patients 35 36…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-related quality of life is a key outcome in the management of LSS and its assessment during clinical practice may suggest the introduction of psychological interventions directed at promoting psychological resources in the patient with the aim to improve long-term outcome or even enhance recovery. Indeed, cognitive-behavioural patient education has been proven effective for the improvement of both clinical and quality-of-life outcomes in these patients 35 36…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of both these aspects during clinical practice may suggest a comprehensive evaluation aimed to improve long-term outcome. For example, patient education and psychological interventions aimed to promote patient’s resources have been proven effective for the improvement of both clinical outcomes and quality of life in these patients 35 36…”
Section: Introductionmentioning
confidence: 99%
“…Hedges' g and 95% CI precluded meta-analysis. In the acute period, two studies 39,43 reported statistically significant improvements in mobility and function. Another trial 31 reported statistically significant improvements in similar functional measures for both subacute and longer term time points.…”
Section: Hedges' Gmentioning
confidence: 99%
“…Patient information, helping to manage expectations, has long been considered a key element of enhanced recovery pathways (ERPs) (Grocott et al 2012) and has traditionally been delivered in surgical and anaesthetic pre-assessment clinics. More sophisticated psychological preparation for surgery, for example using cognitive behavioural education, may provide additional benefit (Rolving et al 2016). As we dissect the functions of the various elements of the pathway to surgery it becomes clear that diagnosis, prognosis and shared decision-making do not have to be undertaken at the same time and place as preparation for surgery.…”
Section: Opportunities To Add Value Before Surgerymentioning
confidence: 99%